A COMPARISON OF LEVELS OF JOB SATISFACTION, ROLE STRESS, AND PERSONAL COMPETENCE BETWEEN UNION MEMBERS AND NONMEMBERS - Odewahn, Charles A.; Petty, M. M. (Academy of Management Journal, 1980)
The study examines the affect of labor union membership on a number of factors including job stress, job satisfaction, self-esteem and employee competence. According to the results of the study, there was a significant reported difference between union members and nonmembers in regards to formal education, organizational tenure and position tenure. The study asserts that union members experience lower levels of job satisfaction, job stress and also display lower levels of personal competence than do nonmembers.